The effect of silicon carbide (SiC) on physical and mechanical properties of recycled aluminium chip AA6061 - Ab Kadir, Muhammad Irfan (2018)
Aluminium alloy AA6061 recycling benefits to the current and future generations by conserving energy and other natural resources. Solid state recycling of AA6061 chips by cold compression is a current approach processing technique that uses remarkably lower energies and operating cost compared to conventional recycling by casting. Thus with the current approach of processing technique by cold compaction technique solid-state recycling made it possible for fabrication of direct recycling chips. In this research, AA6061 chips were recycled to fabricate with SiC (2.5, 5 and 7.5 wt.%) and Al powder (10, 30 and 50 wt.%) by using uniaxial cold compaction at 9 tons for 20 minutes and sintering process at a temperature of 552°C. The effects of the various composition of Al and SiC powder on the microstructure of the recycled AA6061/Al-SiC composites showed that the Aland SiC powders in samples were distributed non-homogeneously between the AA6061 chip regions due to the separation of the two materials and SiC only sits between the gap exist. The density of sample AA6061/1OAl powder gave the closest value to theoretical at 2.43 g/cm3 and decreases when more Al powder was added. Significantly, changes in density can be concluded as increasing sintered density resulted in lower apparent porosity and water absorption. The AA6061/10Al-7.5SiC sample showed the highest hardness at 61.0 Hv because of the hard characteristic of SiC particle. Whereas, the maximum compression strength was at AA6061/10Al-5SiC with 306.5 MPa. The compression strength decreases with increasing amount of Al powder content due to the weak bonding between the particles. Meanwhile, the sample strength increases with increasing the amount of SiC due to the high stiffness of the embedded in SiC. In conclusion, the objective of this study was achieved by the addition of SiC will improve the mechanical properties of recycled aluminium AA6061 composites.